A Low-Cost Light Fidelity Prototype Designed for Patients’ Status Transmission in Benin Hospital - SANYA, MAX FREJUS O.; MAGNIDET, Fifamè Merci-Ange; BANDIRI, Sabi Y.M.; NASSARA, Mètoho Anaïs G. (My University, 2023)
In hospitals, there is a lot of medical equipment’s that is sensitive to monitor patients’ status. In this condition, it is prohibited of using Wi-Fi especially in the case of intensive care unit due to probable interference between Wi-Fi radio waves and hospital operation equipment’s. To overcome such restrictions, this work proposes to design a low-cost LiFi prototype for data transmission between two medical equipment’s in hospital. LiFi is based on LED light bulbs through which data can be transmitted. Meanwhile, it doesn’t interfere with medical equipment’s, since LiFi uses illumination for data transmission. In this paper, we built a prototype using accessible tools and platforms such as Arduino with hardware and software. The designed prototype allows text and image transmission between two equipment’s using an LED and a photodiode. After many experimental tests, we showed the possibility to transmit data rate of 115,200 bits/s throughput over 2,5cm using the LiFi prototype designed. To the best of our knowledge, this is the first Benin LiFi transmission that opens the way for huge possibilities of projects.
Keywords: LiFi; VLC; LED; Arduino